KIAA1429 in non-small cell lung cancer: bridging m6A epigenetics to therapeutic innovation - Liu, Hui; Shi, Ke; Liu, Liang; You, Bo-Hua; Liu, Tao; Ren, Xiao-Fei; Guo, Qiang; Li, Dan (Frontiers in Surgery, 2025)
As a pivotal component of the m6A methyltransferase complex, KIAA1429 plays a critical regulatory role in the pathogenesis of non-small cell lung cancer (NSCLC), driving tumorigenesis, metastasis, and therapeutic resistance through epigenetic mechanisms. Clinically, KIAA1429 overexpression correlates with aggressive disease progression and poor patient prognosis to conventional therapies. This review comprehensively examines the dysregulated expression patterns and functions of KIAA1429 in NSCLC, elucidating its m6A-dependent modulation of key downstream effectors (Such as the HOXA1, DAPK3, and BTG2) that orchestrate malignant transformation. We highlight the emerging potential of KIAA1429 as a novel molecular target for precision therapy in NSCLC.